Youth violence in schools: impacts and its relationship to resilience (Research, Society and Development, 2025)
School violence has reached alarming levels in Brazil in recent years, raising serious concerns about youth mental health. This study aims to investigate the impacts of school violence among adolescents and to explore the potential role of resilience in mitigating its effects. It also considers how strengthening resilience might help shed light on the phenomenon of violence itself. In this qualitative case study, data were collected through document analysis and narrative interviews conducted with teachers and a school counselor at a full-time public school in the municipality of Parintins, Amazonas, Brazil. The findings underscore the need to actively address violence in the school setting, while also pointing to the importance of protective factors at home and the support systems provided by the school itself, which play a key role in helping students navigate everyday challenges and in building their capacity for resilience. The study concludes that promoting mental health and resilience requires an educational approach that is holistic, dialogical, human-centered, and emancipatory, one that actively supports the development of each student's resilience potential.